An Ecological and Evolutionary Framework for Commensalism in Anthropogenic Environments. (August 2016) - Hulme-Beaman, Ardern; Dobney, Keith; Cucchi, Thomas; Searle, Jeremy B.
Abstract : Commensalism within anthropogenic environments has not been extensively discussed, despite its impact on humans, and there is no formal framework for assessing this ecological relationship in its varied forms. Here, we examine commensalism in anthropogenic environments in detail, considering both ecological and evolutionary drivers. The many assumptions about commensalism and the nature of anthropogenic environments are discussed and we highlight dependency as a key attribute of anthropogenic commensals (anthrodependent taxa). We primarily focus on mammalian species in the anthropogenic-commensal niche, but the traits described and selective pressures presented are likely fundamental to many species engaged in intense commensal relationships with humans. Furthermore, we demonstrate that this largely understudied interaction represents an important opportunity to investigate evolutionary processes in rapidly changing environments. Trends: The definition of commensal taxa should be based on dependency. The concept of anthrodependent taxa leads to new species categorised as commensal. Commensals give insight into selective pressures in rapidly changing environments.